Legal Review of the Settlement of Sharia Mortgage Defaults Based on DSN-MUI Fatwa No. 17/DSN-MUI/IX/2000 - Nasution, Emmi Rahmiwita; Muhtadi, Muhamad Ammar; Arini, Rani Eka (Westscience Press, 2025)
This study examines the legal framework governing the handling of defaults in Sharia mortgage contracts, focusing on the interpretation and application of DSN-MUI Fatwa No. 17/DSN-MUI/IX/2000. Using a normative juridical approach, the research analyzes how Islamic financial institutions address customer defaults (wanprestasi) in a manner consistent with Sharia principles and national banking regulations. The study explores the fatwa’s relevance in regulating sanctions, ensuring fairness, and preventing elements of riba while maintaining the stability of the Islamic financial system. The findings reveal that DSN-MUI Fatwa No. 17 provides clear moral and legal guidance for handling defaults through non-ribawi sanctions, such as fines dedicated to social purposes. However, discrepancies still exist between the fatwa’s moral prescriptions and its implementation due to the lack of detailed operational procedures within national law. The study concludes that better integration between Sharia norms, DSN-MUI fatwas, and Indonesian financial regulations is necessary to enhance the effectiveness, justice, and legal certainty in handling Sharia mortgage defaults.